Performance of Cross-Border Acquisitions: Empirical Evidence From Canadian Firms Acquired by Emerging Countries - Zhou, Yang (Université d'Ottawa | University of Ottawa, 2016)
An Increasing number of enterprises from the emerging market countries have become active in cross-border acquisition activities since 2000. Canada is influenced by this emerging countries M&As (mergers and acquisitions) wave. More and more Canadian firms are acquired by emerging country investors so it is necessary to conduct a study on the performance of these M&As. Using the short-term window event study, I analyze security prices of Canadian listed firms acquired by emerging countries from 2000 to 2016. After calculating the abnormal return and cumulative abnormal return of target firms. I find that the abnormal return on the event day is about + 10.3% and the cumulative abnormal return for 11 days is about +10.55%. The finding indicates that in the short term, the performance of Canadian firms which are acquired by emerging countries is positive. Technology and mineral firms have significantly positive abnormal return on day 0 while energy firms only have small abnormal return at the same time.